2005
DOI: 10.1126/science.1108190
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic Transgenerational Actions of Endocrine Disruptors and Male Fertility

Abstract: Transgenerational effects of environmental toxins require either a chromosomal or epigenetic alteration in the germ line. Transient exposure of a gestating female rat during the period of gonadal sex determination to the endocrine disruptors vinclozolin (an antiandrogenic compound) or methoxychlor (an estrogenic compound) induced an adult phenotype in the F 1 generation of decreased spermatogenic capacity (cell number and viability) and increased incidence of male infertility. These eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
2,030
5
35

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,300 publications
(2,137 citation statements)
references
References 26 publications
40
2,030
5
35
Order By: Relevance
“…This study raises the possibility that exposure to ATZ can directly alter the fetal developmental program and that ATZ-induced effects can be inherited across generations. Here we used an outbred CD1 mouse model because outbred mice are more sensitive to toxic exposure than inbred mice (11) and are considered to be better predictors of the human response (106). Pregnant dams (F0) carrying F1 offspring were exposed to the herbicide ATZ between embryonic (E) days E6.5 to E15.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study raises the possibility that exposure to ATZ can directly alter the fetal developmental program and that ATZ-induced effects can be inherited across generations. Here we used an outbred CD1 mouse model because outbred mice are more sensitive to toxic exposure than inbred mice (11) and are considered to be better predictors of the human response (106). Pregnant dams (F0) carrying F1 offspring were exposed to the herbicide ATZ between embryonic (E) days E6.5 to E15.5.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings raise the possibility that histone marks, which are retained in sperm, play a key role in safekeeping epigenetic information for subsequent generations. A groundbreaking work by Skinner laboratory showed that the fetus undergoing gonadal sex determination is particularly vulnerable to environmental exposure that engenders changes in DNA methylation (11). …”
Section: Introductionmentioning
confidence: 99%
“…This latter concept of the epigenetic transmission of a trait through the modification of the infant's genes by maternal behavior has been studied extensively in the area of stress regulation, stress responsiveness, and the hypothalamic-pituitary-adrenal axis, but is yet to be studied in any depth for the hypothalamicpituitary-gonadal axis. The former concept of germline transmission of an epigenetic trait has been most clearly demonstrated in the field of reproductive toxicology, in which Skinner et al showed that prenatal exposure to endocrine-disrupting chemicals causes changes in DNA methylation that were manifested as the latent development of male infertility, reproductive cancers, and other dyfunctions, and that this phenotype is transmitted through the male germline across multiple generations [5,6]. Furthermore, these animals were also behaviorally modified across generations.…”
Section: The Developmental Basis Of Adult Disease and Dysfunctionmentioning
confidence: 99%
“…Estrogen-like molecules could interfere with the physiologic function of endogenous hormones causing, among others, significant effects on the reproductive system both in females and males [102, 103]. This adverse effect is only in part understood, and the wide variability of the results found in the literature depends on the experimental approach, the concentrations tested, the time of exposure and the effects of confounding variables [104].…”
Section: Effects Of Phyto- and Xenoestrogens On Human Breast Tissuementioning
confidence: 99%